Equity in mathematics education in Francophone Sub-Saharan Africa: what levers to activate to leave no child behind ? - (:unkn) unknown (My University, 2024)
Equity in education is at the heart of education systems in both developed and developing countries. In sub-Saharan Africa francophone countries, the quality of mathematical learning is a major issue for many countries, since only 37% of pupils at the end of primary school have the minimum skills required. The aim of this research is to fill the gaps in knowledge about the factors that foster quality and equitable learning in mathematics at the end of primary school inthose countries. Improving the quality of mathematics learning at the end of primary school requires identifying the drivers in these countries to inform decision-making and educational policies. To this end, this research identifies the variables in the four dimensions of equity (access to resources, quality of teachers, learning opportunities, family, and personal characteristics of the pupil) that promote high-quality, equitable learning at the end of primaryschool in those countries. A total of 62,934 pupils at the end of primary school (including 49.1% girls) in 14 countries were considered in the analyses. A logistic regression model and effect size were used to identify variables in the four dimensions of equity that have the greatest effect on mathematical learning at the end of primary school. In the light of these results, proposals are made to ensure quality and equitable education in sub-Saharan Africa francophonecountries.
Keywords: African Research